Image quality dependency on system configuration and tube voltage in chest tomosynthesis—A visual grading study using an anthropomorphic chest phantom. Issue 3 (18th February 2015) - Söderman, Christina; Asplund, Sara; Allansdotter Johnsson, Åse; Vikgren, Jenny; Rossi Norrlund, Rauni; Molnar, David; Svalkvist, Angelica; Gunnar Månsson, Lars; Båth, Magnus
Abstract : Purpose: To investigate the potential benefit of increasing the dose per projection image in chest tomosynthesis, performed at the current standard dose level, by reducing the angular range covered or the projection image density and to evaluate the influence of the tube voltage on the image quality. Methods: An anthropomorphic chest phantom was imaged using nine different projection image configurations and ten different tube voltages with the GE VolumeRAD tomosynthesis system. The resulting image sets were representative of being acquired at the same total effective dose. This was achieved partly by applying a simulated dose reduction to the projection images due to restrictions concerning the tube load settings on the VolumeRAD system. Four observers were included in a visual grading study where the reconstructed tomosynthesis section images were rated according to a set of image quality criteria. Image quality was evaluated relative to the default configuration and default tube voltage on the VolumeRAD system. Results: Overall, the image quality decreased with decreasing projection image density. Regarding angular range covered by the projection images, the image quality increased with decreasing angular range for two of the criteria, whereas for a criterion related to the depth resolution in the section images the reduced angular ranges resulted in inferior image quality as compared to the default configuration. The image quality showed little dependence on the tube voltage. Conclusions: At the standard dose level of the VolumeRAD system, the potential benefits from increasing the dose per projection do not fully compensate for the negative effects resulting from a reduction in the number of projection images. Consequently, the default configuration consisting of 60 projection images acquired over 30° is a good alternative. The tube voltage used in tomosynthesis does not have a large impact on the image quality.